Design of Dual Homing Backup Link on Routing Border Gateway Protocol With Method Hot-Swap Routing Protocol - Heri Bani Jumawan; Subhanjaya Angga Atmaja; Firmansyah Firmansyah; Suminar Suminar; Tuti Rohayati (Budapest International Research and Critics University, 2021)
The importance of the role of the network at this time makes companies and organizations look for ways to keep data flows running without downtime. Application of link backup is one way to overcome this. The need for the use of backup links at this time is expected to ensure the smooth running of the company is running its business. In this study, a design that will use BGP routing as well as using the methods HSRP and VLAN (Virtual Local Area Network) on the switch as supporters. The results obtained from the tests that have been carried out have resulted in the application of a backup link using BGP routing with the method HSRP can provide network availability of almost 0 percent in overcoming interference.